Mari belajar wudhu’: learning wudhu’ through game-based learning for children - Ab Rahman, Muhammad Khairul Haziq; Abd Rahman, Mohd Shukor (College of Computing, Informatics, and Mathematics, 2025)
Ablution ritual is a process to cleansing our body parts before performing prayer or other worship. The body parts which are washing face, washing both arms, wiping part of head and washing both feet. It is important for Muslim society especially for children to learn the ablution process in order to fulfill the needs before performing any worship especially for children. The children are prompted to learn the ablution process so that the children can perform prayer earlier. According to the study, most of the problems among children are lack of enjoyment in learning ablution by using traditional methods and lack of understanding of proper and correct procedure for ablution. This project aims to change that. This project intends to create a web-based desktop application that can help children understand more about ritual ablution process. The goal is to design a storyboard of a game-based learning application that teaches children about ablution, to develop a game-based learning application that teaches children about ablution through game-based learning to understand ablution and to evaluate the enjoyment of the game-based learning application that teaches children about ablution. This project uses Game Development Life Cycle methodology as its methodology is the most suitable for developing this application successfully and smoothen the developer progress. After making the application, the application was evaluated to see if people enjoyed it and if it really helped them understand the ablution process better through a questionnaire based on the scale of e-GameFlow. The results show that the project scores a high percentage of enjoyment, which is 75.60%. The finding suggests that the application needs to improve on increasing enjoyment while learning the ablution process. Future work can be applied to the project by providing the option of Multilanguage to the user.